Internalisasi Nilai Kearifan Lokal Pobinci-Binciki Kuli pada Usahawan Buton dalam Etika Bisnis Syariah untuk Mewujudkan Kesejahteraan - Tamsir Tamsir; Muhammad Wahyuddin Abdullah; Hasaruddin Hasaruddin (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
This study aims to interpret the value of local wisdom of the Buton's natives pobinci-binciki kuli through entrepreneurs and then internalize it in sharia business ethics to achieve prosperity and well beings of the people. The approach used in this study is an ethnographic approach that makes Central Buton as a center of research. The findings in this study are the values of the local wisdom of Buton's island natives pobinci-binciki kuli which can be internalized in Islamic business ethics as follows: Defining value, pomae-maeaka (mutual shame) internalized in nature siddiq (integrity), internalized in value poma-maasiaka (love one another) internalized in nature fatonah (Intelligence), internalized in values of popia-piara (mutual protection) internalized in nature of amanah (trustworthy) and the value of poangka-ngkataka (mutual support) internalized in nature tabligh (communicative). These are the identities inherent in the Prophet Muhammad. when running a business. Therefore, sharia business ethics in real terms have been applied by the people of Central Buton through the local wisdom of Buton's natives, known as the pobinci binciki kuli. These values have brought Central Buton’s entrepreneurs to achieve prosperity oriented to the world and hereafter.